Co‐Intercalation of Dual Charge Carriers in Metal‐Ion‐Confining Layered Vanadium Oxide Nanobelts for Aqueous Zinc‐Ion Batteries. Issue 5 (22nd December 2022) - Lv, Tingting; Zhu, Guoyin; Dong, Shengyang; Kong, Qingquan; Peng, Yi; Jiang, Shu; Zhang, Guangxun; Yang, Zilin; Yang, Shengyang; Dong, Xiaochen; Pang, Huan; Zhang, Yizhou
Abstract: Vanadium‐based oxides with high theoretical specific capacities and open crystal structures are promising cathodes for aqueous zinc‐ion batteries (AZIBs). In this work, the confined synthesis can insert metal ions into the interlayer spacing of layered vanadium oxide nanobelts without changing the original morphology. Furthermore, we obtain a series of nanomaterials based on metal‐confined nanobelts, and describe the effect of interlayer spacing on the electrochemical performance. The electrochemical properties of the obtained Al2.65 V6 O13 ⋅ 2.07 H2 O as cathodes for AZIBs are remarkably improved with a high initial capacity of 571.7 mAh ⋅ g −1 at 1.0 A g −1 . Even at a high current density of 5.0 A g −1, the initial capacity can still reach 205.7 mAh g −1, with a high capacity retention of 89.2 % after 2000 cycles. This study demonstrates that nanobelts confined with metal ions can significantly improve energy storage applications, revealing new avenues for enhancing the electrochemical performance of AZIBs. Abstract : We synthesized a series of metal confined nanomaterials by a one‐step hydrothermal method. The metal ions confined nanobelts can stabilize the layered structure, effectively control the interlayer spacing, and provide a more significant diffusion channel for the intercalation and deintercalation of Zn 2+ without changing the oxide morphology.